Bismuth as a general internal standard for lead in atomic absorption spectrometry - Bechlin, Marcos A. [UNESP]; Fortunato, Felipe M. [UNESP]; Ferreira, Edilene Cristina [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nobrega, Joaquim A.; Donati, George L.; Jones, Bradley T. (Elsevier B.V., 2014)
Bismuth was evaluated as internal standard for Pb determination by line source flame atomic absorption spectrometry (LS FAAS), high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS) and line source graphite furnace atomic absorption spectrometry (LS GFAAS). Analysis of samples containing different matrices indicated close relationship between Pb and Bi absorbances. Correlation coefficients of calibration curves built up by plotting A(Pb)/A(Bi) versus Pb concentration were higher than 0.9953 (FAAS) and higher than 0.9993 (GFAAS). Recoveries of Pb improved from 52-118% (without IS) to 97-109% (IS, LS FAAS); 74-231% (without IS) to 96-109% (IS, HR-CS FAAS); and 36-125% (without IS) to 96-110% (IS, LS GFAAS). The relative standard deviations (n = 12) were reduced from 0.6-9.2% (without IS) to 0.3-4.3% (IS, LS FAAS); 0.7-7.7% (without IS) to 0.1-4.0% (IS, HR-CS FAAS); and 2.1-13% (without IS) to 0.4-5.9% (IS, LS GFAAS). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Universal internal standard; Bismuth; Lead; Atomic absorption spectrometry